Jamaica : Staff Report for the 2001 Article IV Consultation and Review of Staff Monitored Program. (IMF Staff Country Reports; Country Report ;, 2001)
The principal problems facing the Jamaican economy are the extremely heavy burden of public sector debt, low growth, and the legacy of earlier periods of high inflation. The government has implemented several improvements in its debt management strategy. Fiscal restraint has been reinforced by tight monetary policy. Exchange rate stability has succeeded in lowering domestic inflation. The legislative framework strengthens prudential supervision of both banks and other financial institutions to limit the risks of any further financial crisis. Measures to strengthen the regulatory framework are required.